Pembelajaran Model Think Pair and Share: Pengaruhnya terhadap Kemampuan Komunikasi Matematis Siswa pada Materi Himpunan - Tri Haryani; Asra; Andi Kaharuddin (FKIP, Universitas Lakidende Unaaha, 2022)
This study aims to examine the effect of think pair and share cooperative learning model on the mathematical communication skills of the 7th graders of SMPN 1 Puriala on the Set topic. This type of research is quantitative research that is a quasi-experimental (quasi-experimental). The design of this research is The Nonequivalent Posttest-Only Control Group Design. The population of this study was the 7th graders of SMPN 1 Puriala. The Class C (experimental group) and Class B (control group) were then selected as the samples of the study using purposive sampling technique. Paper test and documentation as the instruments were administered in collecting the data. The descriptive and inferential techniques were used in analyzing the data. The descriptive analysis found that the mean score of mathematical communication skill of the experimental class was 52.408 which was higher than mean scored by the control class, 36.400. In addition, the inferential analysis obtained the value of tcount = 6.815 > ttable = 1.671. As a result, H0 was rejected and H1 was accepted. Descriptively, it shows that the mathematical communication skill of the experimental group is higher than the control group after being treated with a think pair and share cooperative learning model. It was concluded that the think pair model has a positively significant effect on the mathematical communication skills in the 7th graders of SMPN 1 Puriala on the topic of set.